Analysis of Susceptance Storey Level Damage of Coral Reefs in Territorial Water of Archipelago in Karimunjawa by Using Geographical Information System - J Jumadi; Kuswaji Dwi Priyono (Universitas Muhammadiyah Surakarta, 2005)
This research aim to determine susceptance storey level damage of coral reefs in Territorial Water of Archipelago of Karimunjawa. Method which used in this research is special data analysis which in the form of data of sekunder by using Geographical Information System. Pursuant to analysis known that research area there are six especial stressor which menace coral reefs for example: Port, Airport, Center Dive, Coastal Wisata, Resident, and Appliance Catch. Pursuant to spasial analysis which have can be determined that equal to 69.50% from entire coral reefs research area in a condition do not susceptance, namely there are in territorial water region of Island: Kembar, Parang, Kumbang, Katang, Nyamuk, Krakal Besar, Krakal Kecil, Geleang, Burung, Bengkoang, Menyawakan, Cemara Besar, Cemara Kecil, Sintok, Gundul, Cendikian, Genting, Seruni, and Sambangan. As for the rest equal to 30.50% enough natural rentan of damage, there are at territorial water of islands owning high resident activity storry level, namely around in Island: Kemujan, Karimunjawa, Menjangan Besar, and Menjangan Kecil.